Numerical Investigation of PTT Fluid Under Bidirectional Extensional Forces and Crystallization Effects - Mercan, Hatice (SPRINGER HEIDELBERG, 2024)
A numerical simulation of the film blowing process is performed. The Phan-Thien and Tanner (PTT) constitutive equations with quiescent and flow-induced crystallization effects are considered with proper boundary and initial conditions. The PTT model is employed both for molten and crystallized polymer. Modeling of crystallization is done with nested Schneider rate equations and the Kolmogorov-Avrami model. The current model can predict the shape and size of the bubbles, as well as their temperature, stress, space filling and morphological changes for given process conditions. The study focuses on investigating the impact of process conditions on the mechanical response of the blown film, as well as on the morphological structure of the crystallizing molten polymer. It is observed that the axial stress increases at a faster rate compared to the circumferential stress with increase in draw ratio. The trend is reversed for increasing blow-up ratios. Increasing the draw ratio does not result in significant improvement in the quiescent contribution to the crystalline structure, but it leads to a decrease in the flow-induced contribution. Increasing blow-up ratio leads to increase in total space filling and the flow-induced component of the crystalline structure. Finally, three heat transfer coefficients chosen from the literature are compared. It is observed that the model choice is not critical for higher draw ratio values, but for low and moderate values, detailed investigations are required. The presented model enables accurate prediction of both the morphological structure and mechanical properties of semicrystalline polymers in a film blowing process.
Keywords: Film blowing; Numerical simulations; Extensional flow; PTT model; Crystallization; Heat transfer coefficients; FILM BLOWING PROCESS; FLOW-ENHANCED CRYSTALLIZATION; NON-NEWTONIAN FLUIDS; TUBULAR FILM; NONISOTHERMAL CRYSTALLIZATION; TRANSIENT SOLUTIONS; STABILITY ANALYSIS; MODEL; VALIDATION; SIMULATION; Science & Technology - Other Topics